Understanding the markets - Loader, David (Operations management series (Securities Institute), 2002)
An analysis of the major securities, derivatives and money markets from an operations point of view, 'Understanding the Markets' takes the reader through the major features and characteristics of the markets and the products. The relationship between the trading and dealing functions and the operations functions is examined and the issues discussed. This book looks at the financial markets from the viewpoint of the person working in the operations functions that support the trading, dealing and investment processes, and as such is essential reading in order to fully understand the industry - an industry which has gone, and is still going through, much change. As the markets undergo change so too do the administration, clearing and settlement functions, as the clearing houses, securities depositories and custodians merge and diversify. This is going to impact on the operations teams that support the trading, sales and retail business. A failure to be aware of and to understand the impact of changes in the markets will create massive problems, greater risk and ultimately financial losses. And yet the sheer size and diversity of the global markets, together with the rapid pace of change and expansion, and the increasing volume of transactions needing to be processed, presents a massive challenge to operations teams and managers. Knowing how the markets work and what impacts on the operations team is crucial for managers and supervisors. In this book the author provides a full explanation of the markets and their impact in operations terms. So if you are about to embark on a career in operations 'Understanding the Markets' is essential reading. Alternatively, if you are planning a career as a dealer it will prove very useful in explaining the process that occurs after you have traded. The definitive series of professional references for those finance professionals concerned with "Back office" or operations management unique to this industry. Presents concise references on the essential management functions such as technology, client services, and risk management for financial operations management professionals. A comprehensive resource from a leading financial management consultant for global banks and institutions